Mundane morality: Gender, categories and complaints in familial neighbour disputes. Issue 2 (27th February 2015) - Stokoe, Elizabeth; Edwards, Derek
Abstract : The paper introduces the concept of 'mundane morality', which refers to the practices of everyday life in which people mix moral evaluations, a sense of right and wrong, blame and culpability, etc., with ordinary accounts and descriptions of persons, actions, and events. Challenging traditional psychological work on moral development, including Gilligan's work on the gendered nature of moral reasoning, we argue that 'morality' is best understood as a communicative practice. Rather than focus on identifying gendered styles of moral reasoning, we show how gender is invoked to do moral work in an episode of recorded neighbour dispute mediation. We analyse the way in which parties make complaints on the basis of gendered category memberships, and show how 'the accountability of social conduct brings directly into focus moral dimensions of language use' (Drew 1998: 295). Overall, we aim to show how to analyse 'moral reasoning' as it happens; as it is imbricated in the daily practices of everyday life.